Association of n-3 polyunsaturated fatty acids and inflammatory indicators with renal function decline in type 2 diabetes. Issue 2 (April 2015) - Chung, Hsin-Fang; Long, Kurt Z.; Hsu, Chih-Cheng; Al Mamun, Abdullah; Jhang, Huei-Ru; Shin, Shyi-Jang; Hwang, Shang-Jyh; Huang, Meng-Chuan
Summary Background & aims The n-3 polyunsaturated fatty acids (PUFAs) and the inflammatory indicator, interleukin-6 (IL-6), have been implied in the development of renal dysfunction. This longitudinal study examined the effect of n-3 PUFAs and IL-6 on the risk of renal function decline and explored whether n-3 PUFAs modify the effect of inflammatory indicators on renal dysfunction risk in type 2 diabetes. Methods Studying 676 type 2 diabetic patients, we analyzed erythrocyte fatty acids and inflammatory markers in 2008 and estimated glomerular filtration rate (eGFR) in 2008 and 2012. Renal function decline was defined as an eGFR decline of ≥25% over a 4-year period. Results Multivariable logistic regression revealed erythrocyte total PUFAs, n-3 PUFAs, and n-3/n-6 PUFA ratio correlated negatively with risk of renal function decline (OR = 0.75, 0.78, and 0.61, respectively, all p < 0.01), while n-6 PUFAs did not. IL-6 independently predicted risk of renal dysfunction (OR = 1.18, p = 0.015). Stratifying erythrocyte PUFAs into low (<50th percentile) or high group (≥50th percentile), we found a positive association between IL-6 and risk of renal dysfunction only in the low n-3 PUFA (OR = 1.27, p = 0.035), low n-3/n-6 PUFA (OR = 1.27, p = 0.034), and low total PUFA groups (OR = 1.36, p = 0.005), but not in the high groups. Conclusions High PUFA concentrations, especially n-3 or higher n-3/n-6 PUFA ratio, may exert protective effects against renal function impairment in type 2 diabetic patients. Whether the effect is mediated via modification of inflammatory biomarker such as IL-6 by high n-3 PUFA status warrants further investigation.